FIRM VALUE IN THE INDONESIAN MINING COMPANY - Mayangsari, Fitria; Suhadak, Suhadak; Dzulkirom. AR, Moch. (Profit: Jurnal Adminsitrasi Bisnis, 2020)
Mining companies listed on the Indonesia Stock Exchange in 2013-2017 are the objects of this study. The value of the company is influenced by capital structure and profitability and the size of the company is the destination to be known. Exploratory is the type in this study by looking at secondary data published by the official website of each mining company. Purposive sampling becomes a data collection technique with a total of 21 mining companies. The results of the study using PLS 3.0 analysis show that firm value is positively influenced by profitability and company size. Capital structure is positively influenced by capital size. Other results from this study indicate that capital structure is not significantly affected by profitability. The value of the company is also not negatively affected by the capital structure.